Dampak Pandemi Covid-19 terhadap Pengangguran, Kemiskinan dan Ketimpangan Pendapatan: Bukti Data Panel di Indonesia - Sri Rosmiati Sani; Cut Dian Fitri; Khairul Amri; Muliadi Muliadi; Ikhsan Ikhsan (Ekonomis: Journal of Economics and Business, 2022)
This study aims to analyze the effect of the COVID-19 pandemic on unemployment, poverty, and income inequality in Indonesia. Using panel data from 34 provinces in Indonesia for the period of 2018.S1-2020.S2, the econometric analysis model applied is panel regression with dummy variables. The study discovered that the Covid-19 pandemic significantly impacts increasing urban poverty and unemployment rates, but not significantly on rural poverty. Using time-series data during the period, it turns out that this pandemic has improved the distribution of income in the community, both in urban and rural areas.